Creating Value through Entrepreneurship in Wellness Gastro Tourism: The Role of Innovation and Experiential Wellness - Lastiani Warih Wulandari; Dewi Turgarini; Meitolo Hulu (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: This research addresses the gap in creating value in wellness gastro tourism through innovation and wellness experiences rooted in Indonesia’s culinary heritage. Objective: This study aims to examine the role of entrepreneurship in creating value through innovation and experiential wellness in the context of wellness gastro tourism. Methods: The study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM)—selected for its suitability in handling complex latent variable models with non-normal data—applied to 312 respondents identified through purposive sampling, representing tourists with direct experience in wellness-based gastronomic tourism in Indonesia. Results: The analysis results show that the R² value for experiential wellness is 0.514, indicating that innovation explains 51.4% of the variation in experiential wellness. Meanwhile, the R² value for value creation is 0.638, indicating that innovation and experiential wellness together explain 63.8% of the variation in value creation. The findings demonstrate that innovation has a positive and significant effect on experiential wellness and, both directly and indirectly, affects value creation. Experiential wellness is proven to act as a mediating variable that strengthens the relationship between innovation and value creation. These findings confirm that value creation in wellness gastro tourism is not only determined by product innovation but also by the quality of holistic experiences perceived by tourists, including physical, emotional, and spiritual dimensions. Conclusion: This study contributes an integrative empirical model linking entrepreneurship, innovation, and experiential wellness, strengthening the role of local wisdom in sustainable tourism innovation. Business actors are recommended to adopt experience-driven and innovation-based strategies to enhance competitiveness in the wellness gastro tourism sector.